Production and sequential optimization of Bacillus subtilis MF467279 pullulanase by statistical experimental designs and evaluation of its desizing efficiency. (April 2018) - Abd El Aty, Abeer A.; Shehata, Abeer N.; Shaheen, Tharwat I.
Abstract: In our search for a pullulanase production from unconventional sources, Bacillus subtilis MF467279 was isolated from the desert plant species Salsola imbricate, that collected from Tur Sinai, Egypt. The optimization of pullulanase enzyme was performed in three stages. First, the two level Plackett-Burman design to screen the medium constituents that significantly affect the enzyme production. Secondly experiment was important for optimization of the most effective constituents using central composite design (CCD). In the third experiment Two–factor–five–level central composite design (CCD) was applied to identify the best initial pH and agitation (rpm) conditions. A maximal enzyme activity of 75.13 U/ml was more than 4.53-folds the activity obtained using the basal medium. Application of partially purified pullulanase enzyme signified that, the fraction contained mixture of pullulanase and amylase was effectively improved the desizing process of fabrics even at lowest dose as indicated from violet scale scale (TEGEWA), weight loss and Scanning Electron Microscopy (SEM).